Reassessing Innovative Work Behaviors during COVID-19 Pandemic: The Impacts of Workplace Spirituality and Psychological Safety Perception - BÜLBÜL, SEÇİL (My University, 2021)
Recent literature has shown the contributions of positivity in organizations, but less is known about the impact of spirituality and safety feelings as an extension of positive psychology on individuals’ innovative work behaviors. Considering the COVID-19 pandemic outbreak, it is suggested that the conditions encouraging employees’ perceptions and attitudes as well as their innovative work behaviors (IWBs) have been changed. Based on the positive psychology approach, workplace spirituality and psychological safety are seen as important factors on employees’ IWBs. Therefore, this study aimed to examine the relationships among perceived workplace spirituality, psychological safety, and employees’ IWBs within the context of the COVID-19 pandemic. Employees working in different private sectors in Istanbul (N= 251) participated in the current research. The statistical analyses revealed that workplace spirituality contributed to employees’ innovative behaviors, and psychological safety fully mediated this relationship. Based on the findings, practical and conceptual implications of this study are discussed and future directions are presented.

Alanyazında yer alan çalışmalarda, pozitifliğin örgütlerdeki olumlu yansımalarına işaret edilmiş, ancak_x000D_ pozitif psikolojinin bir uzantısı olarak maneviyatın ve güvenlik hissinin yenilikçi iş davranışları (Yid)_x000D_ üzerindeki etkisi hakkında yeterli sayıda bulguya ulaşılmamıştır. Buradan hareketle, bu araştırmada, işyeri_x000D_ maneviyatı, psikolojik güvenlik ve çalışanların yenilikçi iş davranışları arasındaki ilişkinin incelenmesi_x000D_ amaçlanmıştır. Ayrıca, COVID-19 salgının gündeme geldiği örgütsel koşullarda, Yid’i oluşturan koşulların_x000D_ ve süreç esnasında çalışanların işyerine ilişkin tutum ve algılarının da farklılık gösterebileceği öngörülmüştür._x000D_ Bu nedenle, çalışmada ele alınan değişkenlerin günümüz çevresel koşullarında çalışanların algı, tutum ve_x000D_ davranışları açısından incelenmesinin alanyazına önemli katkılar sunabileceği düşünülmüştür. Bu bağlamda_x000D_ gerçekleştirilen araştırmaya, İstanbul'da farklı özel sektörlerde çalışan bireyler (N= 251) katılmıştır._x000D_ İstatistiksel analizler neticesinde, işyeri maneviyatının çalışanların yenilikçi davranışlarına katkıda bulunduğu_x000D_ sonucuna varılmıştır. Psikolojik güvenliğin, işyeri maneviyatı ve yenilikçi iş davranışları arasındaki pozitif_x000D_ yöndeki bu ilişkide tam aracılık rolüne sahip olduğu bulgusuna ulaşılmıştır. Analizler sonucunda elde edilen_x000D_ bulguların uygulamaya ve alanyazına yönelik katkıları değerlendirilmiştir.
COVID-19 Salgını Döneminde Yenilikçi İç Davranışlarına Yeniden Bakış: Algılanan İşyeri Maneviyatının ve Psikolojik Güvenliğin Etkileri